Manual compression versus MANTA device for access management after impella removal on the ICU - Cuculi, Florim; Burkart, Philipp; Cioffi, Giacomo; Moccetti, Federico; Madanchi, Mehdi; Seiler, Thomas; Hess, Stefanie; Wolfrum, Mathias; Jeyarasa, Magiliny; Meier, Sonja; Kuzmiakova, Silvia; Hakimi, Maani; et al. (Scientific reports, 2022)
To compare the safety and efficacy of manual compression versus use of the MANTA closure device for access management after Impella removal on the intensive care unit (ICU). The number of patients treated with percutaneous left ventricular assist devices (pLVAD), namely Impella and ECMO, for complex cardiac procedures or shock, is growing. However, removal of pLVAD and large bore arteriotomy closure among such patients on the ICU remains challenging, since it is associated with a high risk for bleeding and vascular complications. Patients included in a prospective registry between 2017 and 2020 were analyzed. Bleeding and vascular access site complications were assessed and adjudicated according to VARC-2 criteria. We analyzed a cohort of 87 consecutive patients, who underwent access closure after Impella removal on ICU by using either the MANTA device or manual compression. The cohort´s mean age was 66.1 ± 10.7 years and 76 patients (87%) were recovering from CS. Mean support time was 40 h (interquartile range 24–69 h). MANTA was used in 31 patients (35.6%) and manual compression was applied in 56 patients (64.4%). Overall access related bleedings were significantly lower in the MANTA group (6.5% versus 39.3% (odds ratio (OR) 0.10, 95% CI 0.01–0.50; p = 0.001), and there was no significant difference in vascular complications between the two groups ( p = 0.55). Our data suggests that the application of the MANTA device directly on the ICU is safe. In addition, it seems to reduce access related bleeding without increasing the risk of vascular complications.